Comparing donor site morbidity between radial and ulnar forearm free flaps: a meta-analysis. Issue 5 (June 2022) - Xu, Qiang; Chen, Peng-Li; Liu, Yi-Hao; Wang, Si-Min; Xu, Zhong-Fei; Feng, Cui-Juan
Abstract: The vascularised forearm free flap is a workhorse flap for the reconstruction of many types of soft tissue defects. However, the difference in donor-site morbidity between the radial forearm free flap (RFFF) and ulnar forearm free flap (UFFF) remains controversial. This study aimed to compare the donor-site outcomes of RFFF and UFFF. We searched PubMed, EMBASE, Web of Science, clinicaltrials.gov, Cochrane Library, and Chinese Biomedical Literature Database up to August 10, 2021, to identify studies on donor-site outcomes of RFFF versus UFFF in patients undergoing reconstructive surgery. Two authors individually extracted data and performed quality assessments of the selected articles. The overall morbidity and overall effect of individual complications of the donor site were analysed. In total, 288 cases from five studies were included in our analysis. The UFFF group was significantly superior to the RFFF group regarding overall morbidity and overall effect of individual complications of the donor site. The morbidity of UFFF donor sites was significantly lower than that of RFFF, and UFFF may be an ideal substitute for RFFF in reconstructive surgery. However, additional large-scale studies are necessary to confirm this finding.